ANALISIS TINGKAT PROFITABILITAS BANK DENGAN METODE RISK BASED BANK RATING - Meliske Sitanaya (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
This research aims to analyze whether the, Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM),) and Capital Adequacy Ratio (CAR) have significantinfluencesimultaneously and partially toward Return On Asset (ROA). This research classifiedthe verifiation research. The population is conventional commercial bank period 2006-2015. Sample was determined by the higher bank asset, a total of ten companies. The secondary data were taken such as from financialreport of Banks started from 2006 until 2015. The technique of data analysis in this research using panel regression analysis. ROA as a dependent variable, NPL, LDR, NIM and CAR as independent variables. Data processing using E-views 6. The result provides evidence that NPL and CAR have significantinfluencesimultaneously toward ROA, while NIM and LDR are not significantinfluencesimultaneously toward ROA. NPL partially have negative significantinfluencetoward ROA, LDR and NIM partially positive are not significantinfluencetoward ROA, and CAR partially have positive significant influence towd ROA.